2004
DOI: 10.1002/art.20135
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of wrist and finger joints in healthy subjects occasionally shows changes resembling erosions and synovitis as seen in rheumatoid arthritis

Abstract: Objective. To explore the presence of changes resembling rheumatoid arthritis erosions and synovitis in metacarpophalangeal (MCP) and wrist joints of healthy individuals on magnetic resonance imaging (MRI) and to compare the MRI findings with conventional radiographic, clinical, and biochemical findings.Methods. Twenty-eight healthy individuals were studied. Contrast-enhanced MRI and conventional radiography of the dominant wrist and second through fifth MCP joints were performed, coupled with standard clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
95
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(109 citation statements)
references
References 25 publications
9
95
0
5
Order By: Relevance
“…Consistent with previously published data (27), small bone changes resembling erosions were observed in some healthy controls. However, none of them had score changes above the SDD and no control subjects had destructive joint changes seen on radiography.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previously published data (27), small bone changes resembling erosions were observed in some healthy controls. However, none of them had score changes above the SDD and no control subjects had destructive joint changes seen on radiography.…”
Section: Discussionsupporting
confidence: 92%
“…These criteria are based on 4 main domains: joint involvement (detected by clinical examination, ultrasonography, or MRI), serology (anti-CCP and RF), acute-phase reactants (CRP level and erythrocyte sedimentation rate), and duration of synovitis. The findings of the present study, in which we demonstrated that changes revealed on MRI of the joints of healthy subjects resembled pathologic features of the RA joint, are in accordance with the results from other MRI studies of healthy subjects (18,19), and thus these findings underscore the need for establishment of a threshold to indicate which types and grades of MRI findings should be used to designate a "positive" result on MRI. Our study was planned, powered, and designed with the ACR 1987 criteria for RA as the standard reference.…”
Section: Discussionsupporting
confidence: 91%
“…The authors explained the difference between MRI and US by the visualization by MRI of the subchondral cysts that were interpreted as erosions. Ejbjerg et al [28] detected low grade erosion-like changes in 2.2% of MCP examined by MRI in 28 normal subjects, especially in the second and the fifth MCP joints. All the lesions were small, without increased signal intensity on postcontrast images.…”
Section: Discussionmentioning
confidence: 99%